A near-infrared view of Nearby Galaxies: The Case of NGC 6300 - Gaspar, Gaia (2019)
We present a near-infrared study of the Seyfert 2 galaxy NGC 6300, based on subarcsecond images and long slit spectroscopy obtained with Flamingos-2 at Gemini South. We have found that the peak of the nuclear continuum emission in the K s band and the surrounding nuclear disk are 25 pc off-center with respect to the center of symmetry of the larger scale circumnuclear disk, suggesting that this black hole is still not fixed in the galaxy potential well. The molecular gas radial velocity curve yields a central black hole upper mass estimation of . The Paβ emission line has a strongly asymmetric profile with a blueshifted broad component that we associate with a nuclear ionized gas outflow. We have found in the K s -band spectra that the slope of the continuum becomes steeper with increasing radii, which can be explained as the presence of large amounts of hot dust not only in the nucleus but also in the circumnuclear region up to r = 27 pc. In fact, the nuclear red excess obtained after subtracting the stellar contribution resembles to that of a blackbody with temperatures around 1200 K. This evidence supports the idea that absorbing material located around the nucleus, but not close enough to be the torus of the unified model, could be responsible for at least part of the nuclear obscuration in this Seyfert 2 nucleus.